AB0197 Evaluation of Serum IL-10 and IP-10 Levels Is Useful as Prognostic Biomarkers for Selection of IL-6R Antibody (TCZ) Prior To Tumor Necrosis Factor (TNF) Inhibitor in Rheumatoid Arthritis Treatment. (15th July 2016) - Kameda, T.; Dobashi, H.; Inoo, M.; Onishi, I.; Kurata, N.; Izumikawa, M.; Takeuchi, Y.; Nakashima, S.; Shimada, H.; Ozaki, H.; Wakiya, R.; Kadowaki, N.
Abstract : Background: Biomarkers of response to treatment in rheumatoid arthritis (RA) are sorely needed given the large inter-individual variability in efficacy of the available drugs. However, there is few reported to distinguish between responses to the different biologics (Bio) 1) . Some authors think it will be difficult to obtain good predictive biomarkers for the efficacy of Bio before administration. Consequently, it is important that we identify the novel biomarker to predict the efficacy of these agents before the administration of Bio. Objectives: To identify a serum biomarker for prediction of the response to Bio in patients with RA, we investigated whether serum cytokine level before treatment with Bio may represent useful prognostic biomarkers for TNF inhibitor (GLM) or IL-6R antibody (TCZ) treatment in bio-naïve RA. Methods: To identify a serum biomarker for prediction of the response to Bio in patients with RA, we performed serum cytokines analysis in RA patients before and after Bio treatment with TCZ and GLM. At the first, we enrolled 10 responder and 10 poor-responder RA patients treated with Bio. 29 cytokines levels before treatment were measured using MILLIPLEX MAP Human Cytokine/Chemokine®. According to analysis of these 29 cytokines, IL-17, IL-6, IL-10 and IP-10 were eliminated as candidates for novel biomarker to predict the effectiveness of RA treatment. Then we enrolled 41 bio-naïve RA patients before administration of TCZ (n=27) or GLM (n=14). We measured these four serum cytokines before and after treatment with each Bio using ELISA. At baseline and 24 weeks after Bio-therapy with TCZ or GLM, we assessed DAS28 and measured serum levels of IL-17, IL-6, IL-10 and IP-10 using commercial ELISA kits. Responders and non-responders were defined as patients who had clinical remission (CR; DAS28 <2.6) and non-CR (DAS28 >2.6) at 24 week after administration of Bio. Wilcoxon two samples test was performed to compare cytokine levels. Results: Mean age was 57.6±15.9, 70.6±14.7 years old and mean disease duration was 77.1±86.2, 114.0±142.6 months in TCZ and GLM patients, respectively. Disease activity of RA was 4.78±0.98 and 4.23±0.76 with DAS28 in TCZ and GLM patients, respectively. In CR group of TCZ (n=19), the serum IP-10 and IL-10 levels decreased compared with non-CR group by ELISA, significantly (P<0.05). As for RA patients treated with TCZ, IP-10 levels were significantly higher in responders. As for RA patients treated with GLM, responders showed a trend toward higher levels of baseline IL-10 compared to non- responders, while IP-10, IL-17 and IL-6 differences did not reach statistical significance. Conclusions: In our study, the serum levels of IP-10 and IL-10 before Bio administration appeared to be associated with favorable responses to TCZ. Furthermore, these cytokines including IP-10 were not associated to response of GLM treatment. It is suggested that bio-naïve RA with low serum IP-10 levels might be treated with TCZ better than TNFi (GLM). References: Gibbons LJ, Hyrich KL. Biologic therapy for rheumatoid arthritis: clinical efficacy and predictors of response. BioDrugs. 2009; 23(2): 111–24. Acknowledgement: None. Disclosure of Interest: None declared